IMPLEMENTATION OF SUSTAINED SILENT READING TO INCREASE FIFTH-GRADE STUDENTS’ READING INTEREST AT SDN 1 PEKANTINGAN - Rizka Amalia; Ani Nur Aeni; Cucun Sunaengsih (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The lack of students’ reading interest is indicated by many students who are more interested in playing with gadgets than reading a book. It is exacerbated by the condition of the library, which has been closed for approximately 5 years so it makes students less facilitated to read. The purpose of this paper is to find out how the implementation of Sustained Silent Reading increases fifth-grade students’ reading interest. The research was conducted at SDN Pekantingan 1 Cirebon. The method used was qualitative research method with study cases and data that are used and produced are descriptive data. Based on the AKM Kampus Mengajar’s pre-test dan posttest, the results indicate that there is a significant value. After implementing Sustained Silent Reading, the students dominantly achieve a significant value. Even though the posttest score did not reach 80, students still managed to obtain a significant score that was higher than the pretest. In conclusion, the implementation of Sustained Silent Reading is effective and can increase students' interest in reading.